Student’s errors in solving set problems for junior high school students based on newman's procedure - Sari, Noviana Puspita; Sukoriyanto, Sukoriyanto; Sulandra, I Made (Universitas Islam Negeri Raden Intan Lampung, 2025)
Errors in solving mathematical problems, especially in the material of sets, are still widely found in junior high schools. This study aims to describe the types of student errors and the factors causing them in solving problems about sets based on the Newman Procedure. The study was conducted on 31 eighth-grade students at one of the state junior high schools in Malang City, with three students (S-1 to S-3) selected as subjects by purposive sampling. The main instrument was the researcher, with supporting instruments in the form of tests and interviews. Data analysis was carried out using the Miles & Huberman model. The results of the study showed that subjects S-1 to S-2 misunderstood the problem (misunderstood what was actually known and asked in the problem incompletely), while S-3 did not. All subjects experienced transformation errors (wrong writing of mathematical models/formulas), process skills (miscalculations/not continuing the procedure), and final answers (wrong conclusions). The main causal factors include lack of reading accuracy, weak conceptual understanding, and errors in calculations and procedures. The implications of this study indicate the need for learning strategies that emphasize conceptual understanding, accuracy, and more systematic procedural solutions.